The Glomerular Endothelium Restricts Albumin Filtration - Ballermann, Barbara J.; Nyström, Jenny; Haraldsson, Börje (Frontiers in Medicine, 2021)
Inflammatory activation and/or dysfunction of the glomerular endothelium triggers proteinuria in many systemic and localized vascular disorders, among them the thrombotic microangiopathies, many forms of glomerulonephritis, acute inflammatory episodes like sepsis and COVID-19 illness, and chronic endothelial dysfunction, for instance, in the chronic cardiorenal syndrome and in metabolic disorders like diabetes. While the glomerular endothelium is a porous sieve that filters prodigious amounts of water and small solutes, it also bars the bulk of albumin and large plasma proteins from passing into the glomerular filtrate. This endothelial barrier function is ascribed predominantly to the endothelial glycocalyx with its endothelial surface layer, that together form a relatively thick, mucinous coat composed of glycosaminoglycans, proteoglycans, glycolipids, sialomucins and other glycoproteins, as well as secreted and circulating proteins. The glycocalyx/endothelial surface layer not only covers the glomerular endothelium, it also extends into the endothelial fenestrae. Some glycocalyx components span or are attached to the apical endothelial cell plasma membrane and form the formal glycocalyx. Other components, including small proteoglycans and circulating proteins like albumin and orosomucoid form the endothelial surface layer and are bound due to the glycocalyx due to weak intermolecular interactions. Indeed, bound plasma albumin is a major constituent of the endothelial surface layer and contributes to its barrier function. A role for glomerular endothelial cells in the barrier of the glomerular capillary wall to protein filtration has been demonstrated by many elegant studies, but it can only be fully understood in the context of other components, including the glomerular basement membrane, the podocytes and reabsorption of proteins by tubule epithelial cells. Discovery of the precise mechanisms that lead to glycocalyx/endothelial surface layer disruption within glomerular capillaries will hopefully lead to pharmacological interventions that specifically target this important structure.